The Impact of Investor Sentiment, Credit Rating, Profitability, and Leverage on Stock Return LQ45 Period From 2017 to 2021 - Drastya Amalia; Dewi Hanggraeni (Syntax Literate, 2022)
The purpose of this research is to identify the effect of investor sentiment, credit ratings, profitability, and leverage on stock returns. This study uses panel data analysis using the Panel Least Square method which is carried out on financial data on 30 companies that are members of the LQ45 composite index during the period 2017 to 2021. In this study, stock returns are the dependent variable, investor sentiment, credit ratings, profitability, and leverage become independent variables, and firm size, book to market ratio, also COVID19 become control variables. The study's findings indicate that the profitability variable has a significant effect on stock returns and other independent variables have no significant effect on stock returns. This study aims to assist investors in identifying and analyzing the variables that influence the company so that investors gain stock returns in the future.